Yeni Türk Edebiyatı’nın Temel Kavramları - Çanaklı, Levent Ali (Türkçe Eğitiminde Temel Kavramlar, 2023)
Yeni Türk Edebiyatı, Türk edebiyatı tarihinin son evresini teşkil eder ve yaklaşık iki asırlık bir geçmişe sahiptir. Batı etkisinde gelişen bu edebiyat, klasik Türk edebiyatından ayrı olarak pek çok ilmî, felsefi ve edebî anlayışın izlerini taşır. Dolayısıyla, Yeni Türk Edebiyatı’nın doğuşunu ve gelişimini anlayabilmek için söz konusu etkileri kavramsal düzeyde tanımak gerekir. Bu bağlamda temel kavramlar belirlenirken Tanzimat’tan sonra toplumsal hayatımıza giren fikirler, ideolojiler, siyasi dönemler, yeni edebî türler ve edebî hareketler, Yeni Türk Edebiyatı’na etkileri ölçüsünde, göz önünde tutulmalıdır. Bu noktada roman, tiyatro, makale gibi yeni türlerin; Servet-i Fünun ve Millî Edebiyat gibi edebî hareketlerin; Batılılaşma, medeniyet, hürriyet, ilerleme gibi kavramların ve Türkçülük, Osmanlıcılık gibi ideolojilerin Yeni Türk Edebiyatı’nın temel kavramları arasında değerlendirilmesi doğru olur.New Turkish Literature constitutes the last phase of the history of Turkish literature and has a history of approximately two centuries. This literature, which developed under Western influence, bears the traces of many scientific, philosophical and literary understandings, apart from classical Turkish literature. Therefore, in order to understand the birth and development of New Turkish Literature, it is necessary to recognize these influences at a conceptual level. In this context, while determining the basic concepts, the ideas, ideologies, political periods, new literary genres and literary movements that entered our social life after the Tanzimat should be taken into consideration, to the extent of their effects on New Turkish Literature. At this point, it would be correct to consider new genres such as novels, plays and articles, literary movements such as Servet-i Fünun and National Literature, concepts such as Westernization, civilization, freedom and progress, and ideologies such as Turkism and Ottomanism among the basic concepts of New Turkish Literature.